Comparing clinical outcomes in upper versus lower lobe endobronchial valve treatment in severe emphysema - Eberhardt, Ralf; Herth, Felix; Radhakrishnan, Sri; Gompelmann, Daniela (Respiration, 2015)
Background: Lung volume reduction surgery has been recommended for patients with upper lobe predominant emphysema and was associated with less favorable outcomes in patients with non-upper lobe predominant emphysema. The value of endobronchial valve (EBV) treatment in lower lobe predominant emphysema has not been studied. Objectives: To confirm the equivalence of upper and lower lobe valve treatments in patients with heterogeneous emphysema. Methods: A retrospective analysis from the Endobronchial Valve for Emphysema Palliation Trial (VENT), where patients with heterogeneous emphysema received Zephyr® EBV (Pulmonx Corp., Redwood City, Calif., USA) or medical treatment, was performed. Patients with low interlobar collateral ventilation and accurate placement of valves in the target lobes were identified. Safety and efficacy were compared between patients who underwent upper versus lower lobe treatment. Results: Of the 331 patients, 60 had low interlobar collateral ventilation and successful lobar exclusion (45 patients with upper lobe treatment and 15 patients with lower lobe treatment). There was no difference in baseline characteristics between the groups except for a higher destruction score (70.3 vs. 60.7%; p = 0.0010) and a higher heterogeneity index (24 vs. 13%; p = 0.0005) for the upper lobe cohort. At 180 days, both groups had improved clinically. There were no significant differences in mean changes or responder rates of forced expiratory volume in 1 s (+23.8 vs. +22.9%), the St. Georges Respiratory Questionnaire (-6.50 vs. -7.53 points), the 6-min walk test (+24.1 vs. +44.0 m), target lobe volume reduction (-1,199 vs. -1,042 ml), or in the adverse event rate between both cohorts. Conclusion: Patients with lower and upper lobe predominant emphysema benefit equally from EBV therapy when interlobar collateral ventilation is low and lobar exclusion is achieved. Patients with lower lobe disease did not have increased adverse events compared to patients with upper lobe emphysema.
Gesehen am 06.07.2020